An efficient, secure and verifiable conjunctive keyword search scheme based on rank metric codes over encrypted outsourced cloud data. (January 2023) - Yousefipoor, Vahid; Eghlidos, Taraneh
Abstract: Public key encryption with keyword search (PEKS) is a cryptographic primitive that allows a secure search for desired keywords of data users by a cloud server using a search token. To the best of our knowledge, we propose the first practical, semantic secure, and post-quantum PEKS scheme based on rank metric codes. The proposed scheme is secure against keyword guessing attack, reaction attack, and key exposure, and enjoys conjunctive keyword search, verifiability of search results using Bloom filter and garbled Bloom filter. We implement the scheme with C++ programming language on a desktop computer. At the security level of 256 bits, the scheme performs all the necessary steps for encryption, keyword search, and verification of search results for one keyword in 22.5 milliseconds. Furthermore, the public key length at this security level is about 5 kilobytes. We show that the scheme is more efficient than the existing relevant post-quantum ones. Graphical abstract: Highlights: A public key with keyword search scheme based on rank metric codes is proposed. The scheme is secure under chosen keyword, keyword guessing, and reaction attacks. The scheme is secure against quantum processors, having a small public key. The scheme supports the verifiability of search results and conjunctive keyword search.